Regenerative Potential of Granulation Tissue in Periodontitis: A Systematic Review and Meta-analysis - Naiwen Tan; Maja Sabalic; Linh Nguyen; Francesco D’Aiuto (Stem Cells International)
Background and Aim. Soft and hard periodontal tissues contain limited numbers of stem cells. This makes regeneration of the periodontium in patients with periodontitis challenging and unpredictable. Granulation tissue is traditionally removed during periodontal corrective therapy, but it is believed to contain multipotent stem cells which could be used for regenerative therapy. The aim of this research was to critically appraise the evidence on cellular components within granulation tissue in patients with periodontitis and its regenerative potential when compared to control healthy periodontal tissue. Methods. Electronic searches were conducted in five databases including CENTRAL, MEDLINE, EMBASE, Web of Science, and Dentistry & Oral Sciences Source using a combination of MeSH terms and keywords up to 21 June 2022. Human studies including patients aged over 18 years with all forms of periodontitis were included. Following the risk of bias assessment, both qualitative and quantitative analyses were performed. Results. A total of twelve studies were included in qualitative analysis and six of them in quantitative analyses. The evidence suggested that cells derived from periodontitis granulation tissue have osteogenic, adipogenic, chondrogenic, neurogenic, and angiogenic differentiation abilities as well as immunoregulatory properties. In particular, CD44+, CD73+, CD90+, CD105+, and CD146+ cells were found widely in granulation tissue whilst the only meta-analysis confirmed that CD90+ cells were present in lower numbers within the granulation tissue when compared with healthy periodontal tissue (WMD=−23.43%, 95% CI -30.43 to -16.44, p<0.00001). Conclusions. This review provided further evidence that granulation tissue from patients with periodontitis can be a potential stem cell source for regenerative therapy.